2019
DOI: 10.4314/njt.v38i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pavement condition index: a case of flexible road pavements on the university of agriculture Makurdi Campus

Abstract: This study assessed the Pavement Condition Index (PCI) of flexible road pavements on the University of Agriculture Makurdi (UAM) Campus. The ASTM D6433 standard manual for assessing flexible road pavement condition manually was adopted. Analysis of results using descriptive statistics revealed that over 65% of the road pavement on the UAM campus were rated within the range of poor to failed state. Some segments at different routes were rated as fair and above (up to good) conditions, these routes and their cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Setyawan et al [25] examined the condition of road performance and remaining service life of some selected road pavements using the Pavement Condition Index (PCI) which is a function of the surface distresses per road section to predict the remaining service life using deflection data obtained from a Falling Weight Deflectometer (FWD) measurements. In Adeke et al [26] assessment of road pavement condition on the Federal University of Agriculture Makurdi Campus was carried out to present classified and quantitative facts to the university management board for maintenance decision. Dabous et al [27] developed a probabilistic distress-based evidential reasoning method for assessing pavement infrastructure condition and rating as the basis for maintenance decisions and budget allocations.…”
Section: Pavement Management Systemsmentioning
confidence: 99%
“…Setyawan et al [25] examined the condition of road performance and remaining service life of some selected road pavements using the Pavement Condition Index (PCI) which is a function of the surface distresses per road section to predict the remaining service life using deflection data obtained from a Falling Weight Deflectometer (FWD) measurements. In Adeke et al [26] assessment of road pavement condition on the Federal University of Agriculture Makurdi Campus was carried out to present classified and quantitative facts to the university management board for maintenance decision. Dabous et al [27] developed a probabilistic distress-based evidential reasoning method for assessing pavement infrastructure condition and rating as the basis for maintenance decisions and budget allocations.…”
Section: Pavement Management Systemsmentioning
confidence: 99%
“…Amongst the several potential causes of flexible pavement failure, [7, 12,13] concluded that poor drainage was the main culprit. Timely rehabilitation of flexible pavements, however, can save overall maintenance costs by over 50% [14].…”
Section: Introductionmentioning
confidence: 99%
“…This is due to its relatively cheap cost of construction and maintenance practice [1][2]. The performance and life cycle of highway road pavement depend on several factors ranging from environmental conditions, traffic load, material properties, age of pavement, original design of pavement structure, construction quality -workmanship, road geometry and maintenance policy over time [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The failure of road pavement manifests as distresses such as fatigue cracks, rutting or permanent deformation, edge failure and potholes which reduce the efficiency or serviceability of the highway occur [3]. The severity and frequency of occurrence of these distresses or defects affects the surface condition and the entire performance of the highway [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation